Pienten lauluja - Parviainen, Lauri, 1900-1949; Karma, Maija, 1914-1999 (Helsinki : WSOY, 2000)
199 kappaletta.
Lisäpainokset: 5. p. 2002.
1. p. 1958.
Soitiinus: melodia.
Keywords: lastenlaulut; laulukirjat